Observation of muonic Dalitz decays of chib mesons and precise spectroscopy of hidden-beauty states - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Glaser, Fabian; Günther, Paul André; et al. (Journal of high energy physics, 2024)
The decays of the χb1(1P), χb2(1P), χb1(2P) and χb2(2P) mesons into the Υ(1S)μ+μ− final state are observed with a high significance using proton-proton collision data collected with the LHCb detector and corresponding to an integrated luminosity of 9 fb−1. The newly observed decays together with the Υ(2S) → Υ(1S)π+π− and Υ(3S) → Υ(2S)π+π− decay modes are used for precision measurements of the mass and mass splittings for the hidden-beauty states.
*The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, G. Frau, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, J. Hu, C.Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M. Schiller, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1105 weitere]
Gesehen am 20.02.2026